EVALUATION OF THE ACTIVITIES OF NON-CREDIT FINANCIAL INSTITUTIONS IN THE MONETARY CIRCULATION OF RUSSIA - E. Bondarovich; A. Zhilkina; O. Revzon (Вестник университета)
The problematic issues, associated with the functioning of non-credit financial institutions, have been considered. Particular attention has been paid to their activities, in terms of money circulation to organizations-operators of payment systems, in terms of credit to microfinance organizations. Presently, issues of evaluating the activities of non-credit financial institutions are the least developed in the scientific and methodological аspects. Based on the role and importance for monetary and credit circulation in the Russian Federation, ensuring the continuity of payments within the Russian economy and beyond, an approach to the currently unsolved problem as the definition of criteria for the effectiveness of these economic agents has been offered. According to the results of the study, directions have been proposed for improving the assessment of the activities of non-credit financial organizations.